Bad intentions - Fossum, Karin, (1954-) (Vintage, 2011)
Early one September three friends spend the weekend at a remote cabin by Dead Water Lake. With only a pale moon to light their way, they row across the water in the middle of the night. But only two of them return.When the body of the third friend is discovered, Inspector Sejer is put in charge of the investigation. He is troubled by the apparent suicide and has an overwhelming sense that the surviving pair has something to hide.Weeks pass without further clues and then, in a nearby lake, the body of another teenage boy floats to the surface...